(untitled) (Bangladesh Medical Journal, 2016)
Breast cancer patients may experience multiple symptoms due to the disease itself, treatment or combination of both. The aim of the present study was to identify group of symptoms experienced by the patients with breast cancer using cluster analysis. We examined symptom profiles of 120 patients with breast cancer who attended a hospital palliative care centre in a tertiary institution. Following symptoms were analyzed: pain, nausea, loss of appetite, constipation, weakness, cough, breathlessness, sleeplessness, lymphedema, sadness, anxiety and depression. Hierarchical cluster analysis was used to identify the natural groupings within the set. We could identify three clusters. Cluster 1 was characterized by pain, depression, anxiety, weakness, sleeplessness and loss of appetite. Cluster 2 comprised of cough, breathlessness, nausea and constipation. Cluster 3 consisted of two symptoms lymphedema and sadness. The results revealed that the patients with breast cancer experienced symptoms that are multiple and clustered together. Neuro-psychiatric symptoms and weakness formed a significant strong relationship. Knowledge obtained from this study can be beneficial for better understanding, assessment and management of symptom clusters in women with breast cancer. It may also help patients to plan ahead for them to seek management of concurrent symptoms to improve their quality of life. Bangladesh Med J. 2016 Jan; 45 (1): 25-30